Reminiscent capillarity in subnanopores - Irena Deroche (Nature Portfolio, 2019)
Confined fluids in porous media exhibit different behaviors in large and small pores, the crossover between the two regimes being not well understood. Here the authors show, by experiments and simulations, that capillarity is reminiscent even for very small pore diameters, providing a unified picture.